YO SI PUEDO: A CUBAN LITERACY PROGRAM TO STRENGTHEN LITERACY LEVEL IN WEST PAPUA, INDONESIA - Yawan, Hendri (Sanata Dharma University Yogyakarta, 2022)
Illiteracy remains a serious problem in West Papua, Indonesia. The data from Indonesian Central Bureau of Statistics (BPS) show nearly 30 percent of Indigenous Papuans aged between 15 to 45 are illiterate (BPS, 2016). The number is far higher than the national average which is only 3.5 percent (BPS, 2016). In response to the problem, the article aims to provide a brief picture of causes and effects behind the high illiteracy rate in West Papua and to recommend a relevant solution for the problem. The methodology undertaken in this article is a literature review. Relevant literatures are obtained through peer-reviewed articles from reliable journals and any other relevant sources. The results reveal three main factors that contribute to the low literacy level in West Papua; geographical challenges, low human resources and diverse vernacular languages. Due to the high illiterate percentage, Papuan community has been experiencing serious health issue, poverty, poor educational access and low social cohesion. The article also proposes a so-called Yo Si Puedo (YSP) as an alternative non-formal literacy program to strengthen basic literacy in West Papua. It is because YSP can be highly adaptable to the Papuan context in terms of language, culture and social reality.